Pengaruh penutupan arteri renalis terhadap kadar ion-ion Na, K, Ca dan jumlah eritrosit, trombosit serta hematokrit pada anjing - Bambang Soejatno Bambang Soejatno (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
The effect of renal artery occlusion on the blood concentrations of sodium, potassium and calcium as well as on the amount of red blood cells, blood platelets and hematocrite were studied in dogs. Twenty dogs, both sexes, were 'used in this experiment. The dogs were anesthetized with ketalar and chloralose. The systemic blood pressure was continously monitored during the experiment. The experiment was done under normal systemic blood, left renal artery occlusion,, and on both renal arteries occlusion. The dogs were divided into four groups according to both sexes and body weight. The results showed that during the occlusion of renal artery the blood pressure increased (6.27 - 18.28%). The increase of systemic blood pressure was followed by the increase of the amount of red blood cells, blood platelets and hematocrite. The serum electrolytes concentration of sodium of both increased or decreased. The concentration of potasium and calcium decreased and increased respectively. The concentrations of sodium, potassium and calcium in the urine decreased during the occlusion of the renal artery.Key Words: renal artery occlusion - erythrocytes - blood platelets - urine electrocytes - blood electrolytes